2018
DOI: 10.1111/mec.14483
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics in the wild: Hibernation physiology in free‐ranging dwarf lemurs

Abstract: Hibernation is an adaptive strategy some mammals use to survive highly seasonal or unpredictable environments. We present the first investigation on the transcriptomics of hibernation in a natural population of primate hibernators: Crossley's dwarf lemurs (Cheirogaleus crossleyi). Using capture-mark-recapture techniques to track the same animals over a period of 7 months in Madagascar, we used RNA-seq to compare gene expression profiles in white adipose tissue (WAT) during three distinct physiological states. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 83 publications
1
43
0
Order By: Relevance
“…), [108][109][110][111][112] American black bears (Ursus americanus), 113,114 little brown bats (Myotis lucifugus) 115 and recently in two different species of dwarf lemurs (Cheirogaleus medius and Cheirogaleus crossleyi). 21,116 These studies reveal specific genes that might play a key role in the hibernation phenotype and similar pathways are upregulated in predictable ways in all hibernating species studied to date. Of import are genes involved in lipid and carbohydrate metabolism, blood coagulation, and circadian rhythms.…”
Section: Box 3 Genetic Basis Of Hibernationmentioning
confidence: 91%
See 1 more Smart Citation
“…), [108][109][110][111][112] American black bears (Ursus americanus), 113,114 little brown bats (Myotis lucifugus) 115 and recently in two different species of dwarf lemurs (Cheirogaleus medius and Cheirogaleus crossleyi). 21,116 These studies reveal specific genes that might play a key role in the hibernation phenotype and similar pathways are upregulated in predictable ways in all hibernating species studied to date. Of import are genes involved in lipid and carbohydrate metabolism, blood coagulation, and circadian rhythms.…”
Section: Box 3 Genetic Basis Of Hibernationmentioning
confidence: 91%
“…19,20 Differences in the physiological tuning of hibernation and metabolic regulation may, in fact, signal variation in underlying mechanisms brought about by unique evolutionary histories, though it is increasingly thought that the capacity for heterothermy is ancestral in mammals, having been suppressed in lineages and species that are apparently nonheterothermic. 21…”
mentioning
confidence: 99%
“…Originally thought to be restricted to cold-adapted mammals, hibernation has also been observed in primates (dwarf lemurs; Blanco, Dausmann, Ranaivoarisoa, & Yoder, 2013;Dausmann, Glos, Ganzhorn, & Heldmaier, 2004), implying that perhaps we humans have the ability to hibernate, which has beneficial applications in medicine and longterm space exploration (Chouker, Bereiter-Hahn, Singer, & Heldmaier, 2019). Central metabolic roles for pyruvate dehydrogenase kinase isoenzyme 4 (Faherty, Villanueva-Canas, Blanco, Alba, & Yoder, 2018) and hibernation-specific protein (HP20 complex; Kondo et al, 2006) have been suggested as ancestral 'hibernation signatures' that contribute to mammalian brain signalling and neuroprotection.…”
Section: Building a Better Brain; Lessons From Naturementioning
confidence: 99%
“…sib). NPY2R is a gene that was identified to be upregulated in the fat vs torpor phases of Faherty et al (2018); NPY2R was identified in an introgressed region between C. med/C. sib.…”
Section: Functional Implications Of Ancient Admixture For the Hibernamentioning
confidence: 99%